2013
DOI: 10.1155/2013/259187
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell-Like Cells Derived from Mouse Induced Pluripotent Stem Cells Ameliorate Diabetic Polyneuropathy in Mice

Abstract: Background. Although pathological involvements of diabetic polyneuropathy (DPN) have been reported, no dependable treatment of DPN has been achieved. Recent studies have shown that mesenchymal stem cells (MSCs) ameliorate DPN. Here we demonstrate a differentiation of induced pluripotent stem cells (iPSCs) into MSC-like cells and investigate the therapeutic potential of the MSC-like cell transplantation on DPN. Research Design and Methods. For induction into MSC-like cells, GFP-expressing iPSCs were cultured wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 42 publications
1
29
0
1
Order By: Relevance
“…Himeno et al . have demonstrated that iMSCs from mice exhibited characteristic mice MSC surface marker such as CD105, CD140a, Sca‐1 and CD44 as previously described . The immunosuppressive, cytoprotection and tissue regeneration properties are exerted by the paracrine factors secreted by the MSCs .…”
Section: Phenotypic Features Of Imscssupporting
confidence: 56%
“…Himeno et al . have demonstrated that iMSCs from mice exhibited characteristic mice MSC surface marker such as CD105, CD140a, Sca‐1 and CD44 as previously described . The immunosuppressive, cytoprotection and tissue regeneration properties are exerted by the paracrine factors secreted by the MSCs .…”
Section: Phenotypic Features Of Imscssupporting
confidence: 56%
“…More recently, revertant keratinocytes of a junctional epidermolysis bullosa patient with compound heterozygous COL17A1 mutations used an iPSC approach to generate genetically corrected keratinocytes (155). In addition, iPSCs have been shown to ameliorate diabetic polyneuropathy (a neuropathic disorder associated with diabetes mellitus) in mice (156), and to activate an angiogenic response in mice with hindlimb ischemia (157). …”
Section: From Repair Mechanisms To Clinical Approachesmentioning
confidence: 99%
“…53 The transplanted cells in hindlimb muscles and peripheral nerves of mouse model for diabetic polyneuropathy (DPN), ameliorated nerve conduction velocities, plantar skin blood flow, increased the number-to-muscle fiber ratios, suggesting that iPS-MSC transplantation might have therapeutic effects on DPN through secreting angiogenic/neurotrophic factors and differentiation to Schwann cell-like cells. 54 Moreover, recent studies have further support the use of iPS in skin regeneration. The authors successfully used human keratinocyte-derived iPSCs to reconstitute skin in vitro for the treatment of recessive dystrophic epidermolysis bullosa.…”
Section: Induced Pluripotent Stem (Ips) Cellsmentioning
confidence: 95%